The internal supply chain of operation and green sustainability - Salih, Waleed Khalid; Noor Fareen Abdul Rahim, Essia Ries Ahmed, (Opción, 2019)
The purpose of this paper is to explain and understand how green sustainability in the internal supply chain is achievable in a multinational corporation involved in the manufacturing industry with the corporation of corporate and stakeholders. This study adopts a qualitative study approaches hence the study is limited to secondary data and interviewee validation compared to theoretical models. As a result, Intel had created a strong governance structure that allows a vertical and horizontal team aligning themselves to achieve the vision and strategies set by the corporate. In conclusion, agility in the structure significantly improves collaboration in achieving environmental values.